Urban socio-environmental problematic: state of the art from the national symposium on urban geography (2013 and 2015) - Silva, Francisco Jonh Lennon Tavares; Aquino, Cláudia Maria Sabóia de (Geosaberes; Vol 9 No 18 (2018): May - Aug., 2018)
This article proposes to analyze the state of the art about the urban socio-environmental problematic in the context of National Symposium on Urban Geography (SIMPURB), covering the particularities from which urban social-environmental problems have been thematized. The temporary clipping comprised the years of 2013 and 2015. The methodology included a bibliographic review based on the hypothetical-deductive method and the content analysis technique. The analysis showed a set of particularities underlying the subject matter in focus, with emphasis on investigations of socio-environmental conflicts, risks, vulnerabilities, urban resilience solid waste issues and water resources degradation. These multiple possibilities of approach highlight the diversity and complexity of brazilian geographic production in relation to socio-environmental issues inherent in urban spaces.
Keywords: Problemas socioambientais urbanos. Tendências temáticas. Estado da arte. SIMPURB.